OUTBACK PARTS OF SOCIAL ARRANGEMENT BEING RITUAL ART STAGE IN THE MALAY PELALAWAN RIAU - Nursyirwan Nursyirwan; Delfi Enida (LPPMPP Institut Seni Indonesia Padangpanjang, 2019)
This research globally examines sounds and deals with the fact that inland tribes functioned in medical rituals that were transformed into stage art entertainment. Certain sounds and movements by the Inland Tribe in medicine have meaning and importance. Why the sounds were functioned in a medical ritual which was later changed the function of medicine in the interior to stage art. How is the interaction and form in the ritual of treatment that requires sounds. Research wants to give the same social attention to art and culture to the tribal civilization, which is sometimes considered backward. This research answers the social prejudices of the transfer of treatment locations from the interior to the stage art. The research technique / method uses qualitative techniques with studies in ethnomusicology, ethnography, art anthropology and art sociology. In the study found a management system that leads to a new theory of